2015
DOI: 10.1128/jvi.03454-14
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Interactions between the NS4B and NS3 Proteins of Dengue Virus

Abstract: Flavivirus RNA synthesis is mediated by a multiprotein complex associated with the endoplasmic reticulum membrane, named the replication complex (RC). Within the flavivirus RC, NS4B, an integral membrane protein with a role in virulence and regulation of the innate immune response, binds to the NS3 protease-helicase. NS4B modulates the RNA helicase activity of NS3, but the molecular details of their interaction remain elusive. Here, we used dengue virus (DENV) to map the determinants for the NS3-NS4B interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
100
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 36 publications
6
100
1
1
Order By: Relevance
“…Since NS4B functions as an essential component of the viral replication complex, the inhibitors could function by interfering with protein-protein interactions during viral RNA synthesis. In line with this hypothesis, NS4B was recently reported to oligomerize itself (18) as well as to interact with NS1 (24), NS3 (25,26), and NS4A (27). Besides binding to viral proteins, NS4B is also expected to interact with host factors during viral replication.…”
Section: Discussionmentioning
confidence: 67%
“…Since NS4B functions as an essential component of the viral replication complex, the inhibitors could function by interfering with protein-protein interactions during viral RNA synthesis. In line with this hypothesis, NS4B was recently reported to oligomerize itself (18) as well as to interact with NS1 (24), NS3 (25,26), and NS4A (27). Besides binding to viral proteins, NS4B is also expected to interact with host factors during viral replication.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies reported that mutations in DENV NS4B adversely affect viral genome replication, strongly supporting the fact that NS4B is a component of the replication complex (4)(5)(6). Additionally, NS4B was found to interact with other NS proteins, such as NS3 and NS4A in DENV (7)(8)(9). Re-cently, NS4B was shown to have genetic and physical interactions with NS4A and NS1 in the related flaviviruses Japanese encephalitis virus (JEV) and West Nile virus (WNV), and these interactions were essential for viral genome replication (10,11).…”
mentioning
confidence: 68%
“…We speculate that loss of glycans may affect the structure of NS4B, most probably in the N-terminal luminal domains, and the compensatory abilities of the aromatic amino acid (tyrosine or phenylalanine) within the Asn-58 glycosylation acceptor motif, the alanine at the amino acid (aa) 66 position, or the threonine at the aa 137 position play a significant role in correcting the structural defect of NS4B N58QN62Q. A recent study showed the presence of an interaction between the cytosolic loop of NS4B (aa 129 to 165) and NS3 protein (9). It is possible that NS4B N58QN62Q mutation alters the conformation of the cytosolic loop and disrupts NS4B-NS3 interaction, and different compensatory mutations might correct the conformation of the cytosolic loop, rebuilding the interaction with NS3.…”
Section: Discussionmentioning
confidence: 99%
“…(iv) WNV NS4A regulates the ATPase activity of NS3 helicase (25), while DENV NS4B interacts with the helicase domain of NS3 and dissociates it from singlestrand RNA (26). As noted in the accompanying article by Zou et al (27), the DENV NS3-NS4B interaction was mapped to the NS3 helicase (subdomains 2 and 3) and the NS4B cytoplasmic region (amino acids 129 to 165). (v) NS4A and NS4B genetically interact with NS1 to modulate viral replication.…”
mentioning
confidence: 96%